2010
DOI: 10.1126/science.1196188
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Single-Crystal X-ray Structure of 1,3-Dimethylcyclobutadiene by Confinement in a Crystalline Matrix”

Abstract: Legrand et al . (Reports, 16 July 2010, p. 299) reported the experimental observation of square-planar and rectangular-bent geometries of 1,3-dimethylcyclobutadiene (Me 2 CBD) confined within a crystalline matrix. However, we found no evidence for the Me 2 CBD formation. We argue that the experimental x-ray density data are better attributed to the bicyclic β-lactone intermediate where carbon dioxide is covalently bound to cyclobutadiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…All these factors lead to what is called "poor" data quality. Data quality can indeed lead to alternative interpretations, as illustrated by the comments of Scheschkewitz (2) and Alabugin et al (3). However, we show below that our interpretation is more likely.…”
mentioning
confidence: 48%
See 3 more Smart Citations
“…All these factors lead to what is called "poor" data quality. Data quality can indeed lead to alternative interpretations, as illustrated by the comments of Scheschkewitz (2) and Alabugin et al (3). However, we show below that our interpretation is more likely.…”
mentioning
confidence: 48%
“…Scheschkewitz (2) and Alabugin et al (3) contend that our structures instead correspond with a bicyclic b-lactone intermediate. Our view on the importance of the quality of the x-ray data on structure resolution and the view of the Technical Comment authors coincide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[12,13] However, this finding initiated heated debate in literature on whether the measured crystal structure corresponds to 1,3-dimethylcyclobutadiene at al. [14][15][16][17] Valence bond isomerism of cyclobutadiene has also aroused considerable interest of theoretical chemists, to mention only the most recent high level computational studies by Balkova and Bartlett, [12] Sancho-Garcia et al, [18] Shen et al, [19] Lefrancois et al, [20] and our research group. [13] We have shown that the barrier for automerization reaction of the parent CBD molecule obtained at the MR-AQCC level of theory including extrapolations to the basis set limit is 6.3 kcal mol −1 .…”
Section: Introductionmentioning
confidence: 99%